SHRINKING PROJECTION METHOD WITH ALLOWABLE RANGES FOR ZERO POINT PROBLEMS IN A BANACH SPACE - Ibaraki, T.; Kajiba, S. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2025)
In this paper, we study the shrinking projection method with allowable ranges introduced by Takeuchi (J. Nonlinear Anal. Optim, 10:83-94, 2019) for the zero point problem. We obtain strong convergence theorems for finding a zero point of a maximal monotone operator in a Banach space. Using our results, we discuss the convex minimization problem.